Bilateral extramedullary adrenal plasmacytoma: case report and review of the literature. (May 2017) - Townend, Philip J; Kraus, Gabriel; Coyle, Luke; Nevell, David; Engelsman, Anton; Sidhu, Stan B
Extramedullary plasmacytoma (EMP) accounts for only 3% of plasma cell malignancies; others include multiple myeloma, plasma cell leukemia and solitary plasmacytoma of bone. The majority of EMPs are found in the upper respiratory tract. Other sites include the GI tract, bladder, CNS, thyroid, breast, testes, parotid gland, lymph nodes and skin. There are eight cases in the literature of adrenal plasmacytoma, however, only two were bilateral. We describe our recent experience of bilateral adrenal plasmacytoma and review of the literature. While EMP may present as aggressive locally destructive lesions, excellent local control can be achieved in a majority of cases. Follow-up should be lifelong due to risk of progression to multiple myeloma.